The relationship between supply chain management activities and firm performance with the mediating and moderating effect - Phutthiwat Waiyawuththanapoom; Wissawa Aunyawong; Kajornpong Poolsawad; Veerayuth Thumawongchai; Chanathat Boonrattanakittibhumi; Kittisak Jermsittiparsert (My University, 2022)
The performance plays a key role in the long-term survival of the organizations. If the performance of the organization increases, then the organization may lead in the global perspective. There are various factors that could lead to the performance. Among those, the supply chain management practices (SCMP) play an important role to increase the performance. The SCMP factors may also enhance the competitive advantage of the organizations. Furthermore, the manager support may provide insight to manage the SCM activities which could aid enhance firm performance (FP). Therefore, the purpose of this study is to investigate the relationship between the SCMP and FP with the moderating and mediating effect in the chemical industry of Thailand. The data was collected from the supply chain managers by using a simple random technique. The SEM direct effect shows that SCMA had a significant and positive connection with firm performance FP. In addition, SCMP does not seem to have any significant relationship with the competitive advantage. While competitive advantage has a positive and significant effect on FP. On the other hand, the indirect effect shows that SCMP and FP relationship were partially mediated from the competitive advantage. Moreover, the manager's support did not significantly moderate the SCMP and FP relationship. The current study added literature in the extant literature in the form of empirical findings which could help the researchers explore their studies in future. The study may also provide help to owners as well as to shareholders to know about the importance of the SCMP, competitive advantage and managers' support to increase their FP.
Keywords: Quality and Supply Management